Afrontamiento individual en la calidad de vida laboral del personal de enfermería. - Amaguaya Pacalla, Yadira Lisset (2024)
Coping and quality-of-life are variables interconnected to the daily life activities of nursing professionals due to the role they play in the health system, providing personalized care and emotional support to patients, therefore the work they perform can cause stress which negatively affects their quality of life. In this context, it is essential to adopt health-promoting behaviors that contribute to improve working life quality. Aim: To determine the effectiveness of nursing educational interventions based on individual coping strategies to improve the quality of working life of these professionals. Materials and methods: A research focused on a quantitative descriptive analysis was carried out, based on data obtained from scientific documents published in indexed journals such as Llilacs, Scopus, BVS, Scielo and Redalyc, which allowed collecting information of research interest on the topic studied. Results: it was determined that nursing personnel suffer from Burnout syndrome due to the stress they experience, therefore, coping strategies are proposed to improve the quality of life in mental, physical, emotional, and labour realms. Conclusions: With the research conducted we proceed to identify the coping strategies according to groups levels of care contributing to the promotion of a healthy work environment allowing the improvement of working life quality of the nursing staff.